Impact of e-Governance on Democratic Decentralization in India - Ahmed Raza (KILA Journal of Local Governance, 2015)
The e-governance initiatives have come a long way since the advent of the World Wide Web. This paper explores how the application of Information & Commu- nication Technology (e-Governance) has made Indian democracy decentralized. This concept has its origins in India during the seventies with a focus on development of in-house government applications in the areas of defence, economic monitoring, planning and the deployment of IT to manage data intensive functions related to elections, census, tax administration etc. The efforts of the National Informatics Centre (NIC) to connect all the distre-governance headquarters during the eighties was a very significant development. This paper also focuses on advantages and disadvantages of e-Governance in the system.